Does Breast Cancer Subtype Impact Margin Status in Patients Undergoing Partial Mastectomy?. Issue 7 (July 2022) - Horattas, Ileana; Fenton, Andrew; Gabra, Joseph; Mendiola, Amanda; Li, Fangyong; Namm, Jukes; Solomon, Naveenraj; Gass, Jennifer; Lum, Sharon; Murray, Mary; Howard-McNatt, Melissa; Dupont, Elisabeth; et al.
Background: Molecular subtype in invasive breast cancer guides systemic therapy. It is unknown whether molecular subtype should also be considered to tailor surgical therapy. The present investigation was designed to evaluate whether breast cancer subtype impacted surgical margins in patients with invasive breast cancer stage I through III undergoing breast-conserving therapy. Methods: Data from 2 randomized trials evaluating cavity shave margins (CSM) on margin status in patients undergoing partial mastectomy (PM) were used for this analysis. Patients were included if invasive carcinoma was present in the PM specimen and data for all 3 receptors (ER, PR, and HER2) were known. Patients were classified as luminal if they were ER and/or PR positive; HER2 enriched if they were ER and PR negative but HER2 positive; and TN if they were negative for all 3 receptors. The impact of subtype on the margin status was evaluated at completion of standard PM, prior to randomization to CSM versus no CSM. Non-parametric statistical analyses were performed using SPSS Version 26. Results: Molecular subtype was significantly correlated with race ( P = .011), palpability ( P = .007), and grade ( P < .001). Subtype did not correlate with Hispanic ethnicity ( P = .760) or lymphovascular invasion ( P = .756). In this cohort, the overall positive margin rate was 33.7%. This did not vary based on molecular subtype (positive margin rate 33.7% for patients with luminal tumors vs 36.4% for those with TN tumors, P = .425). Discussion: Molecular subtype does not predict margin status. Therefore, molecular subtype should not, independent of other factors, influence surgical decision-making.